Mental health status and associated factors prevailing among the patients having orofacial clefts in Bangladesh: A mixed method study (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Patients with craniofacial anomalies endure various psychological distress. This study assessed the mental health status and related factors among the patients with cleft lip and/or palate in Bangladesh.Methods: This case-control study was conducted at the Department of Orthodontics, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, over a four-year period. Treated and untreated patients were recruited. A validated DASS-21 questionnaire was used to determine the depression, anxiety and stress levels. In-depth and key informants’ interviews included 16 and 7 participants, respectively. Participants were taken purposively from Bangabandhu Sheikh Medical University, Dhaka, Bangladesh; Sheikh Hasina National Institute of Burn and Plastic Surgery, Dhaka, Bangladesh, and Bangladesh Specialized Hospital, Dhaka, Bangladesh.Results:  Among the 105 cleft patients, 55 were treated, and 50 were untreated. The overall (Median and interquartile range) depression rate was 2 (0–6) versus 28 (24–32), anxiety 4 (0–6) versus 16 (12–18), and stress 6 (4–8) versus 20 (16–24) in treated and untreated groups (P